2010
DOI: 10.1063/1.3327334
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the sheet resistance and conductivity of thin epitaxial graphene and SiC films

Abstract: Single postdielectric resonators operating on their quasi TE011 modes were used for the measurement of the surface resistance and conductivity of graphene films grown on semi-insulating SiC substrates. With this technique the surface resistance was measured with an uncertainty of ±5% and the conductivity was evaluated with an uncertainty equal to the uncertainty in determining the film thickness. The room temperature conductivity of the graphene films proved to be in the range 5×106 to 6.4×106 S/m.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 5 publications
3
74
0
1
Order By: Relevance
“…A 13 GHz dielectric resonance oscillator (DRO) measurement (spot frequency) of multilayer graphene on SiC was made by Krupka, but the per layer conductance was not determined [13,14]. An on-chip coplanar waveguide measurement technique was recently employed to study single-layer graphene (SLG) up to 110 GHz [15].…”
Section: Introductionmentioning
confidence: 99%
“…A 13 GHz dielectric resonance oscillator (DRO) measurement (spot frequency) of multilayer graphene on SiC was made by Krupka, but the per layer conductance was not determined [13,14]. An on-chip coplanar waveguide measurement technique was recently employed to study single-layer graphene (SLG) up to 110 GHz [15].…”
Section: Introductionmentioning
confidence: 99%
“…There have been some studies on measuring the conductivity of graphene based on resonance methods that obtained results in the microwave frequency range. 9,10 Unfortunately, these methods only works at certain discrete frequencies and cannot easily be used to obtain frequency-dependent conductivity properties in a broad frequency band. In our previous work, the relative permittivity of graphene was determined up to 6 GHz using a graphene-on-CPW structure.…”
Section: © 2016 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…In the latter, we have shown that electrical conductivity arises due to hopping of electrons between the localized states provided by the graphene sheets. From the above, it can be seen that so far electrical conductivity involving graphene has been investigated either in its percolative configuration [15] or in a composite structure [10,11]. In the present work, our objective is to study the conduction mechanism in a graphene based polymer composite, where the graphenes will be at close proximity to each other but not in percolative configuration.…”
Section: Introductionmentioning
confidence: 99%